Pengaruh Permintaan Uang Kartal dan Transaksi Uang Elektronik Terhadap Inflasi di Indonesia Tahun 2011-2020 dengan Perputaran Uang Sebagai Variabel Moderasi - Asri Gusriyanti; Jean Elikal Marna (Jurnal Salingka Nagari, 2022)
This study aims to determine how the effect of demand for real money as seen from the amount of real money in circulation and electronic money transactions seen from electronic money volume data on inflation in Indonesia in 2011-2020 with the velocity of money as an moderating variable. Data shows that the demand for real money and electronic money transactions has continued to increase in the last ten years. However, inflation data tends to be stable from 2015-2020 with the policy of reducing energy subsidies (fuel and electricity). This study uses multiple regression analysis method to see the effect of demand for real money and electronic money transactions on inflation in Indonesia. And using the Moderated Regression Analysis (MRA) analysis method to see whether the velocity of money variable can moderate the effect of demand for real money and electronic money transactions on inflation in Indonesia. The results of this study show that: (1) The demand for real money has no significant effect on inflation in Indonesia. (2) Electronic money transactions have no significant effect on inflation in Indonesia. (3) The demand for real money and electronic money transactions has no significant effect on inflation in Indonesia. (4) The velocity of money cannot moderate the effect of demand for real money on inflation in Indonesia. (5) The velocity of money cannot moderate the effect of electronic money transactions on inflation in Indonesia.